Intravenous drug use and AIDS prevention. - Schuster, C R (1988)
Research programs of the National Institute on Drug Abuse take a broad approach to investigating the problems of intervention in intravenous drug use and its relation to the AIDS epidemic. Current prevention strategies are directed to reducing the rates of infection and the progression among the infected to clinical symptoms. Programs test alternative prevention models and focus on the epidemiology of the problem and on basic studies of specific high-risk behaviors. Ultimately, the problem requires community involvement to encourage behaviors which will reduce exposure on the part of drug users, their sexual partners, and their children.